Factor V Q506 (Resistance to Activated Protein C) and Prognosis after Acute Coronary Syndrome - Holm, Johan; Hillarp, Andreas; Zöller, Bengt; Erhardt, Leif; Berntorp, Erik; Dahlbäck, Björn (Thrombosis and Haemostasis, 1999)
Factor V:Q506 causing resistance to activated protein C (APC-resistance), is a risk factor for venous thrombosis. Some studies have indicated an association with arterial disease, especially in women. We investigated the prevalence of the FV:Q506 allele prospectively in 295 patients with acute coronary syndrome. Mortality and myocardial infarction rate were evaluated after 30 days and after 2 years. The FV:Q506 allele was found in 38 patients. In a Cox proportional hazards model, smokers carrying FV:Q506 had a higher risk of infarction or death within 30 days, compared to non-smokers with a normal genotype (relative risk 2.9 [95% CI 1.2-7.0]). The difference remained significant after 2 years (relative risk 2.8 [95% CI 1.2-6.5]). The effect of the FV:Q506 allele on clinical outcome in acute coronary syndrome has not previously been described. Our results demonstrate a gene-environment interaction between smoking and the FV:Q506 allele, with an increased risk of early complications after an acute ischemic event.